2017
DOI: 10.1177/0894439317710435
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Web Content and Web Accessibility at Universities

Abstract: This research assesses whether universities from varied cultures rank significantly different with respect to the quality of their web contents and with regard to their web accessibility (WA) level. Moreover, this article tests whether universities, which make stronger efforts to improve the quality of their web contents, also take into account WA issues to ease the access to such contents. We use a database containing 399 universities from 16 countries. Main results suggest that universities in Anglo-Saxon co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…One benefit of W-A is considerably higher content quality. There is a significant relationship between the level of accessibility and the quality of the web contents (Lorca et al, 2018).…”
Section: Willingness To Support Web Accessibilitymentioning
confidence: 99%
“…One benefit of W-A is considerably higher content quality. There is a significant relationship between the level of accessibility and the quality of the web contents (Lorca et al, 2018).…”
Section: Willingness To Support Web Accessibilitymentioning
confidence: 99%
“…A comparative web accessibility testing could be the criteria to measure the accessibility issues with respect to various evaluation methods [18]. A theoretical based assessment relative to content high quality was brought with respect to their accessibility degree [19]. It has taken into consideration internet sites of 19 poly technique and 40 university websites of Portugal and determined some usual checkpoint mistakes in the procedure of internet content accessibility examination [21].…”
Section: Fig 7 Distribution Of Selected Papers Based On Influencingmentioning
confidence: 99%
“…Besides previously mentioned research on educational websites, several studies have addressed accessibility on education. Freire, de Mattos, Barroso and Santos [32] and Lewthwaite & Sloan [33] introduced accessibility in engineering studies; Seale, Georgeso, Mamas and Swain [34] and Dowrick, Anderson, Heyer and Acosta [35] demonstrated that in UK and USA respectively, students with different capacities have difficulties with technical environments in higher education; the accessibility of different LPs was analyzed including Blackboard [36] or Moodle [37], or compared like in the study of the accessibility between open source (Moodle) and proprietary (Sakai) LPs [38]; a study of 399 universities analyzed the relationship between web content quality and web accessibility in 16 countries [39]. The study concluded that Anglo-Saxon countries pay more attention to web accessibility, while Germanic countries pay more attention to web content.…”
Section: Introductionmentioning
confidence: 99%